A practical guide to over‐the‐counter treatments for hyperpigmentation - Mustufa Jafry; Linna L. Guan; Tasneem F. Mohammad (Wiley, 2024)
Abstract Hyperpigmentation of the skin, defined as increased melanin in the epidermis, is a common condition associated with psychosocial impairment and decreased quality of life. Prescription options are often not covered by insurance and can be cost prohibitive. As such, many turn to over‐the‐counter (OTC) products for treatment. However, a plethora of options are available, which can be confusing. This review aims to evaluate the evidence for common ingredients found in OTC products for management of hyperpigmentation and provide guidance for optimal use to clinicians and consumers. To perform this review, a comprehensive literature search utilizing PubMed and Google Scholar was conducted to identify relevant studies on the clinico‐epidemiological aspects of hyperpigmentation, including postinflammatory hyperpigmentation (PIH), melasma and maturational hyperpigmentation, as well as on relevant OTC treatments. The efficacy and safety of OTC products were assessed based on available evidence, clinical trials and expert recommendations. Our results showed hyperpigmentation is more prevalent among individuals with darker skin types (Fitzpatrick skin phototypes III-VI). Due to limited insurance coverage and the high cost of prescription options, over‐the‐counter (OTC) treatments are widely used for managing postinflammatory hyperpigmentation (PIH). However, the lack of strict regulation by the US Food and Drug Administration (FDA) raises concerns about the safety and efficacy of these products. By critically evaluating the existing literature, this review offers practical, evidence‐based guidance for the selection and utilization of OTC products for the treatment of hyperpigmentation.